2000
DOI: 10.1002/(sici)1098-2795(200001)55:1<117::aid-mrd16>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Both fertilization promoting peptide and adenosine stimulate capacitation but inhibit spontaneous acrosome loss in ejaculated boar spermatozoa in vitro

Abstract: Both fertilization promoting peptide (FPP) and adenosine stimulate capacitation and inhibit spontaneous acrosome loss in epididymal mouse spermatozoa; these responses involve modulation of the adenylyl cyclase (AC)/cAMP signal transduction pathway. However, it was unclear whether these responses were restricted to the mouse or possibly common to many mammalian species. To address this question, the response of boar spermatozoa to FPP and/or adenosine was evaluated. FPP is found in nanomolar concentrations in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 27 publications
2
26
1
Order By: Relevance
“…As the control to NT embryos, in vitro maturation, fertilization and culture (IVMFC) of porcine oocytes as described by Miyoshi et al (1999) was performed to produce blastocysts. The IVF medium also contained 2.0 mM caffeine to induce capacitation and spontaneous acrosome reactions of boar spermatozoa (Funahashi et al 2000).…”
Section: Experimental Studiesmentioning
confidence: 99%
“…As the control to NT embryos, in vitro maturation, fertilization and culture (IVMFC) of porcine oocytes as described by Miyoshi et al (1999) was performed to produce blastocysts. The IVF medium also contained 2.0 mM caffeine to induce capacitation and spontaneous acrosome reactions of boar spermatozoa (Funahashi et al 2000).…”
Section: Experimental Studiesmentioning
confidence: 99%
“…It has recently been demonstrated that both adenosine and FPP can regulate the function of freshly ejaculated and frozen-thawed boar spermatozoa (Funahashi et al 2000b). Replacement of caffeine with adenosine or FPP in the fertilization medium in a conventional IVF system improved monospermic penetration by frozen-thawed boar spermatozoa (Funahashi et al 2000c, Funahashi & Nagai 2001.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that a combination of preincubation of fresh spermatozoa with adenosine and a transient co-incubation IVF system is effective at narrowing the window of sperm penetration and increasing the incidence of oocytes penetrated by a single spermatozoon. Adenosine stimulates and prevents the capacitation and spontaneous acrosome reaction of boar spermatozoa respectively, via the adenylyl cyclase/cAMP pathway (Funahashi et al 2000b). In the presence of adenosine, the timing of in vitro penetration of frozen-thawed spermatozoa appears to be slower than that in the presence of caffeine (Funahashi & Nagai 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allegrucci et al [2001] showed that the A 1 adenosine receptor in human spermatozoa is coupled to Ga i2 and mobilizes calcium stores via IP 3 . It has been proposed that FPP receptors interact with adenosine receptors to help activate the AC=cAMP signaling pathway [Funahashi et al 2000]. Angiotensin II receptors are located on the acrosomal cap region and the flagella of both murine and human spermatozoa resulting in the phosphorylation of both the sperm head and tail via the AC=cAMP=PKA pathway [Mededovic and Fraser 2004].…”
Section: Involvement Of 'First Messengers' In Capacitationmentioning
confidence: 99%